Augmented Reality for Interactive Experiences in Museums: A Review - Shi, Yunzhen; Maszura Abdul Ghafar,; Mohd Faiz Yahaya, (Advances in Humanities and Contemporary Studies, 2024)
Declining interest of visitors towards museum exhibits are causing museum to be vestige and dire. There is a need to personalized museum experiences through the exhibited artifacts display value. This desktop study uses a systematic review from the Scopus and IEEE XPLORE databases over ten years (2014 to 2023). The purpose of the paper is to identify what is the best Augmented Realities (AR) interaction for museum spaces. The discussion will be based on methods or tools to AR interactions, manifestations of AR interaction in museum spaces, and interaction modalities in museum spaces. This study found that when intelligent terminals are used to digitalize virtual exhibits together with wearable devices, it could create interactive gamified multi-mode interfaces for user-exhibit experiences. The outcomes of this paper would aid museums’ design curators to utilize AR interaction and yield visitors interest toward learning and entertainment of museum artifacts.